Prototipe Sistem Rekam Data Alat-alat Ukur, Takar, Timbang dan Perlengkapannya Berbasis RFID - Kumala, Ardelia Ruciragati (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2024)
In metrological supervision, the method of recording data on Measuring Instruments, Measures, Scales, and Equipment (UTTP) still uses conventional methods by writing or typing data on surveillance forms. Generally, retrieving data for one UTTP takes about 2 minutes at the earliest. This time is only for data recording and does not include the allocation of time for technical testing so that it becomes an obstacle if the number of supervised UTTPs amounts to hundreds or thousands. To reduce the duration of data recording, in this study a prototype design of a UTTP data recording system based on Radio Frequency Identification (RFID) was carried out. The data communication system on the proposed prototype uses an On-The-Go (OTG) connection between the smartphone and Arduino UNO. This allows MFRC522 RFID modules connected to Arduino to access RFID data without the need for an external power supply and access to the network. The prototype features data storage on smartphone memory in Microsoft Excel format. Testing on the designed prototype includes data access to RFID tags in the form of cards, keys, and stickers. Based on the test, the maximum time required for the process of reading and writing data on RFID tags is 0.56 seconds, shorter than the conventional method which requires 124.56 seconds. RFID systems can detect tags up to a maximum angular tilt of 135º and can still function with barrier media in the form of plastic, wood, and cardboard.